My First Little House Books: My Little House Book of Animals - Wilder, Laura Ingalls ([S.l.] : HarperCollins Publishers, Inc, 1998)
Summary: Uses characters from the Little house books of Laura Ingalls Wilder, along with simple illustrations and text, to describe some of the animals encountered on the frontier.
Keywords: Animals -- Fiction; Frontier and pioneer life